IMPLIKASI PUTUSAN MAHKAMAH KONSTITUSI NO. 15/PUU-XII/2014 TERHADAP PUTUSAN BADAN ARBITRASE DI INDONESIA - Musa Taklima (Et-Tijarie, 2018)
The purpose of this study was to determine the legal interpretation methods used by the Constitutional Court in resolving the case No. 15 / PUU-XII / 2014 and the implications of the decision contained in the decision No. 15 / PUU-XII / 2014. This type of research used in this study is the library with the doktirnal approach, relying on secondary data sources consisting of primary legal materials, secondary and tertiary techniques all of which are obtained rehabilitated and reconstructed by the literature and analyzed using content analysis. The results of this study indicate that the first, the method used legal interpretation by the Constitutional Court in resolving the case No. No. 15 / PUU-XII / 2014 is the grammatical and systematic method of interpretation. The second implication of the decision of the Constitutional Court No. 15 / PUU-XII / 2014 is resulting in increasingly easy and trivial to appeal cancellation of the arbitral award in Indonesia. Besides the implications that can be raised of the Court's decision is causing its reduced one of the privileges of the arbitration institution final and binding decision that could give birth to skepticism even doubt the people (inside and outside the country) to arbitration in Indonesia.Penelitian ini memiliki tujuan untuk mengetahui metode interpretasi hukum yang digunakan oleh Mahkamah Konstitusi dalam menyelesaikan perkara No. 15/PUU-XII/2014 dan Implikasi putusannya yang termuat dalam putusan No. 15/PUU-XII/2014. Jenis penelitian yang digunakan dalam penelitian ini adalah pustaka dengan pendekatan doktirnal yang bertumpu kepada sumber data sekunder yang terdiri dari bahan hukum primer, sekunder dan tersier yang kesemuanya didapat mellaui teknik studi pustaka dan dianalisis menggunakan teknik content analysis. Adapun hasil penelitian ini menunjukkan bahwa pertama, metode interpretasi hukum yang digunakan oleh Mahkamah Konstitusi dalam menyelesaikan perkara No. No. 15/PUU-XII/2014 adalah metode interpretasi gramatikal dan sistematis. Kedua implikasi dari adanya putusan Mahkamah Konstitusi No. 15/PUU-XII/2014 ini adalah mengakibatkan semakin mudah dan gampangnya melakukan permohonan pembatalan putusan arbitrase di Indonesia. Selain itu implikasi yang bisa dimunculkan dari putusan Mahkamah ini adalah menyebabkan tereduksinya salah satu keistimewaan dari lembaga arbitrase yang putusannya final dan mengikat yang bisa melahirkan kesangsian bahkan keraguan masyarakat (didalam dan luar negeri) terhadap arbitrase di Indonesia.Keyword: Implication, Decision Of The Constitutional Court, Decision Of The Arbitration Agency